Pendampingan Penyusunan dan Penerapan Prosedur Operasional Standar (POS) untuk Meningkatkan Kualitas Produksi pada Industri Percetakan di Gedangan Sidoarjo (Asosiasi Riset Ilmu Teknik Indonesia, 2023)
Production quality in the printing industry is highly influenced by process consistency and the implementation of clear operational standards. A common issue faced by small and medium-scale printing industries, including those in Gedangan, Sidoarjo, is the absence of systematically developed Standard Operating Procedures (SOP), which leads to inconsistent production results and low operational efficiency. This Community Service Program (PKM) aims to provide assistance in the development and implementation of SOPs to improve production quality. The method employed is a participatory approach involving problem identification, SOP development, socialization and training, implementation, and evaluation stages. The results indicate a 25% increase in workers' understanding based on pre-test and post-test results. Additionally, there was a reduction in production errors and improvements in the consistency of print quality and work efficiency. Therefore, the implementation of SOPs has proven effective in enhancing production quality and operational performance in the printing industry sustainably.